Home monitoring of transcutaneous oxygen tension in the early detection of hypoxaemia in infants and young children. Issue 6 (June 1991) - Poets, C F; Samuels, M P; Noyes, J P; Jones, K A; Southall, D P
Abstract : Twenty three patients (age range 0.5-40 months) with recurrent cyanotic episodes underwent physiological recordings, including transcutaneous oxygen tension (TcPO2) from a monitor modified for use at home (Kontron 821S). Of 69 episodes in which the arterial oxygen saturation (SaO2, Nellcor N200) was less than or equal to 80% for greater than or equal to 20 seconds and/or central cyanosis was present, the TcPO2 monitor alarmed (less than or equal to 20 mmHg or 2.67 kPa) in every episode. The pulse oximeter identified hypoxaemia in 62 out of 69 episodes, failing in seven episodes due to signal loss from movement artefact. In only seven of 69 episodes was there an accompanying apnoeic pause (greater than or equal to 20 seconds), and heart rate fell to less than or equal to 80 beats/minute in only five of 28 episodes in which an electrocardiogram was recorded. In 32 episodes in which SaO2 fell to less than or equal to 60%, the TcPO2 monitor alarmed after a median time interval of 16 seconds (maximum time interval 30 seconds). The TcPO2 monitor was then used in an uncontrolled trial at home in 350 patients at increased risk of sudden death and/or hypoxaemia. Indications for monitoring included apparent life threatening events or cyanotic episodes (n = 163), prematurity and prematurity related disorders (n = 86), and sudden unexpected death in one or more siblings (n = 122). The TcPO2 monitor detected cyanotic episodes at home in 81 patients, 52 of whom received vigorous stimulation and/or mouth to mouth resuscitation. Twenty one of these 52 patients had further hypoxaemic episodes documented in hospital with pulse oximetry. In 30 patients, the TcPo2 monitor also identified the gradual development of hypoxaemia, as confirmed by pulse oximetry. Twenty of these needed additional inspired oxygen and six subsequently needed ventilatory support in hospital. This TcPo2 monitor is a reliable detector of both sudden and gradual onset hypoxaemia and is able to be used by parents in the home.